Synthesis and characterization of copper sulfide nanoparticles in hexagonal phase lyotropic liquid crystal - Khiew, P.S.; Radiman, S.; Huang, N.M.; Ahamd, M.S. (2004)
Copper sulfide nanoparticles were prepared in lyotropic hexagonal phase consisting of poly (oxyethelene) 5 nonyl phenol ether (NP5), poly (oxyethelene) 10 nonyl phenol ether (NP10), cyclohexane and aqueous solutions. The stability of the hexagonal phase, which was employed as the reaction template, has been determined by polarizing microscopy, small-angle X-ray scattering (SAXS) and rheology measurement. The optical observation showed that the hexagonal phase liquid crystal system still presented the characteristics spherulitic and focal conic texture after the growth reaction. In addition, there was giving no significant changes on the rheological response of the surfactant system after the formation of the copper sulfide nanoparticles. SAXS data showed that the microstructure dimensions of the surfactant aggregates were preserved and not affected by the growth reaction inside the systems. The final products were characterized by energy filter transmission microscopy, energy dispersive X-ray analysis and UV-visible absorption spectroscopy. The results showed that the size and morphology of the nanoparticles obtained were greatly affected by the reaction aging time. The presence of quantum confinement effect was apparent for the resulting nanoparticles as the estimated optical band-gap energy increased markedly with the decrement of the particles size. Â© 2004 Elsevier B.V. All rights reserved.